Effectiveness of Home Care Interventions in Patients with Moderate to Severe Craniocerebral Injury Combined with Epilepsy - Zhang, Luo-luo; Jiang, Zi-juan; Li, Yuan-yuan; Li, Ping; Hua, Zhan-yan; Zhou, Qian; Cao, Feng (Computational and mathematical methods in medicine, 2022)
Objective. To investigate the effect of a home care model on coping style and quality of life of patients with postcranial surgery complicated by epilepsy. Methods. One hundred and forty-four patients with postcranial surgery complicated by epilepsy admitted to our hospital from July 2017 to April 2018 were selected as study subjects and randomly divided into 63 cases each in the observation group and the control group. The control group was given nursing interventions including health education, psychological intervention, medication guidance, complication prevention, and follow-up management, while the observation group was jointly given collaborative family nursing interventions. At a follow-up of 6 months, indicators such as coping style, treatment compliance, and quality of life were compared between the two groups. Results. Patients in the observation group had significantly higher problem solving, help seeking, and rationalization scores and significantly lower self-blame scores than the control group (P<0.01); significantly higher treatment compliance than the control group (P<0.01); and significantly higher social functioning, emotional well-being, and energy/fatigue scores than the control group (P<0.01). Conclusion. The home care model helps to promote the development of positive coping styles, improve treatment compliance, and improve the quality of life of patients after cranial surgery.